Engineered Sialylation of Pathogenic Antibodies In Vivo Attenuates Autoimmune Disease - Pagan, Jose D. (Cell, 2017)
Self-reactive IgGs contribute to the pathology of autoimmune diseases, including systemic lupus erythematosus and rheumatoid arthritis. Paradoxically, IgGs are used to treat inflammatory diseases, in the form of high-dose intravenous immunoglobulin (IVIG). Distinct glycoforms on the IgG constant fragment (Fc) dictate these divergent functions. IgG anti-inflammatory activity is attributed to sialylation of the Fc glycan. We therefore sought to convert endogenous IgG to anti-inflammatory mediators in vivo by engineering solubilized glycosyltransferases that attach galactose or sialic acid. When both enzymes were administered in a prophylactic or therapeutic fashion, autoimmune inflammation was markedly attenuated in vivo. The enzymes worked through a similar pathway to IVIG, requiring DC-SIGN, STAT6 signaling, and FcγRIIB. Importantly, sialylation was highly specific to pathogenic IgG at the site of inflammation, driven by local platelet release of nucleotide-sugar donors. These results underscore the therapeutic potential of glycoengineering in vivo.